STRATEGI INDIA MENGHADAPI HEGEMONI TIONGKOK DI KAWASAN ASIA SELATAN 2005-2014 - Hetri Pima Anggara; Den Yelta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This paper describes strategy of India’s facing China hegemony in the South Asia region 2005-2014. India and China are two neighbours countries which always compete each other. To protect demands on energy security, China build hegemony in South Asia by investing in strategic infrastructure project (port, highway, railways) and implementing String of Pearls strategy. India found that China hegemony encircling India’s territories, and become threat directly to India’s interest in South Asia region and Indian Ocean especially.To analyze the research question, researcher applied Neo-realism perspective about Security Dilemma and Geopolitics theory. Theoretical framework on this research is guided by qualitative explanation methods. Writing technique in this research is through by library research. The data sources used in this research collected from books, journals, official publication, news from websites and newspaper.Strategy of India’s to counter China hegemony are by established defense cooperation with United States and increase its military capability. India and United States has a common concern with China influence in South Asia, in defense cooperation both countries have been increasing their joint exercises, two-ways trade, and opportunities of technology transfer as rebalance power toward China. India annually raise up defense budget to modernize military capabilities. As part of strategic, India projecting its military presence in Indian Ocean with Andaman and Nicobar as metal chain and active in marine forum as part of maritime diplomacy.Key word: String of Pearls, hegemony, South Asia, Indian Ocean